Архитектоника эмоций и субъективная логика национальной истории в прозе Тараса Шевченко (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article examines the prose of Taras Shevchenko in the context of a new model of historicism, the formation of a national narrative based on post-colonial rhetoric, speech mimicry, muted resistance to the official imperial discourse. Prose is presented as the most convenient way to develop a specifically politicized language, with the help of which a nation pronounces itself in a narrative, in its emotional matrices, historical reminiscences. The story „Naymichka” is analyzed in the aspect of everyday refraction of history, translation of collective emotional experience, its spatial deconstruction. Melancholy and resentment are considered as narrative formations that shed light on Ukrainian history and the post-traumatic experience generated by it. Emphasis is placed on its inescapability in the conditions of colonialism and hybrid identity. The topological analysis of emotions contributes to the understanding of the national landscape through the prism of the internalization of history in the mental structures of the individual.